An overview of the epidermal growth factor receptor fluorescence in situ hybridisation challenge in tumour pathology. Issue 4 (3rd December 2008) - Martin, V; Mazzucchelli, L; Frattini, M
Abstract : Epidermal growth factor receptor (EGFR) is deregulated in a variety of solid malignant tumours. Due to the availability of specific targeted therapies, the request to evaluate EGFR in neoplastic tissues in pathology is dramatically increasing. In analogy to HER2, EGFR evaluation by FISH seems to be superior than immunohistochemistry to select patients for targeted therapies. However, the lack of consensus on how to assess the presence and extent of EGFR gene status deregulation in tissue sections has generated a confusion of inadequately defined criteria, which impairs the quality of communication in both routine patient care and research studies. The objectives of this review are: (1) to analyse methodological aspects, signals evaluation and interpretation criteria related to the detection of EGFR alterations by FISH in cancer samples, highlighting technical limits and controversies; (2) to review the literature concerning EGFR FISH on formalin-fixed paraffin-embedded tissue sections from different types of solid tumours, with a particular focus on the clinical significance of numerical EGFR gene alterations with respect to targeted therapies. Further advances in improving the quality of care of patients with cancers characterised by EGFR gene deregulation will depend on answering some of the questions underlined throughout this overview.